Lipopolysaccharide supports maintaining the stemness of CD133+ hepatoma cells through activation of the NF-κB/HIF-1α pathway. Issue 2 (10th August 2016) - Lai, Fo-Bao; Liu, Wen-Ting; Jing, Ying-Ying; Yu, Guo-Feng; Han, Zhi-Peng; Yang, Xue; Zeng, Jian-Xing; Zhang, Hang-Jie; Shi, Rong-Yu; Li, Xiao-Yong; Pan, Xiao-Rong; Li, Rong; et al.
Highlights: LPS, an important mediator in liver tumor environment, contributes to the stemness maintenance of CD133 + liver CSCs. The results indicate that LPS supports the maintenance of CSCs stemness through signaling of the NF-κB/HIF-1α pathway. LPS/NF-κB/HIF-1α signaling system may act as a potential target for future development of effective therapy to treat HCC. Abstract: Due to the existence of cancer stem cells (CSCs), persistence and relapse of human hepatocellular carcinoma (HCC) are common after treatment with existing anti-cancer therapies. Emerging evidence indicates that lipopolysaccharide (LPS) plays a crucial role in aggravating HCC, but information about the effect of LPS on CSCs of HCC remains scant. Here, we report that the stemness of CD133 + CSCs sorted from the human HCC cell line Huh7 was maintained well when cells were cultured with LPS. The reduction of CD133 expression was much lesser in cultured CSCs in the presence of LPS. In response to LPS stimulation, CSCs showed an increase in their activity of clonogenesis and tumorigenesis. LPS also supported maintaining CSC abilities of migration, invasion, and chemo-resistance. Treatment with HIF-1α-specific siRNA significantly reduced CD133 expression by CSCs at both mRNA and protein levels. Further, the expression of HIF-1α and CD133 was reduced in LPS-stimulated CSCs when the NF-κB inhibitor was added to the cell culture. HIF-1α-specific siRNA also effectively counteracted the effect of LPS on maintaining CSC abilities of migration and invasion. These data indicate that LPS, an important mediator in the liver tumor microenvironment, supports the maintenance of CSC stemness through signaling of the NF-κB/HIF-1α pathway. Our current study highlights LPS as a potential target for developing new therapeutic approaches to eliminate CSCs during the treatment of HCC.